How to develop native plant communities in heavily altered ecosystems: examples from large‐scale surface mining in Germany. Issue 2 (4th December 2013) - Tischew, Sabine; Baasch, Annett; Grunert, Harald; Kirmer, Anita; Prach, Karel
Abstract Questions Does site alteration caused by mining impede spontaneous colonization of native species assemblies to the advantage of neophytic species at the landscape unit and plant community scale? To what extent can mined site conditions support the establishment of rare plant species assemblies that are locally novel but of regional conservation value? What effects have dispersal limitation and stochasticity on spontaneous succession trajectories and how does community structure and composition differ between actively restored sites and ancient grasslands? Location Central German Lignite Mining District. Methods We used comprehensive databases to compare floristic composition in mined sites and their surroundings. At the community level, we choose a chronosequence approach to analyse spontaneous colonization of target species into mined sites and the development of calcareous grasslands, compared to ancient as well as actively restored grasslands. Statistical analyses involved Mann–Whitney U‐test, GNMDS and binary logistic regression. Results The proportion of neophytes in spontaneously developing mined sites was low and similar to the unmined surroundings at the landscape unit as well as plant community scale. Mined sites harbour an impressive number of native and even rare species. However, plant communities lacking immigration of target grasses typical for calcareous grasslands lead to divergences regarding species and functional composition compared to ancient calcareous grasslands. In contrast, plots with actively introduced target species at the onset of succession show a generally more rapid trajectory towards ancient grasslands. The probability of establishing in mined sites increases with higher abundance of calcareous dry grassland species in the vicinity, indicating the importance of high propagule pressure in a landscape context, whereas long‐distance dispersal traits were significant, but less important. Conclusions Spontaneous succession supports the development of native plant communities. However, because of propagule limitation, colonization processes may lead to novel species assemblies. While dispersal stochasticity during spontaneous succession results in a higher γ‐diversity, species introduction supports faster trajectories towards desired reference states providing important ecosystem services such as erosion control. The key decision of whether to rely on spontaneous succession or not mainly depends on the surrounding landscape matrix and history, the need for erosion control and/or rapid compensation for lost habitats.